Partizipatives Kulturmanagement: Interdisziplinäre Verhandlungen zwischen Kunst, Kultur und Öffentlichkeit - Lang, Siglinde (transcript, 2015)
Art-makers make art – and cultural managers make culture? This book begins with an interdisciplinary differentiation of artistic and cultural production, and moves community co-management into the center of the cultural process of meaning. Participatively active cultural managers are called upon, above all, to moderate those liminal spaces evoked by art as sites of negotiation of that which is, and that which could be, as polyphonic spaces of the production of meaning, oriented towards dissensus. Out of an analysis of participatory art projects, Siglinde Lang develops an understanding of cultural management which mediates between the hegemonic and alternative cultural inscriptions of meaning.